Nurse‐led interventions to manage hypertension in general practice: A systematic review and meta‐analysis. (4th March 2022) - Stephen, Catherine; Halcomb, Elizabeth; Fernandez, Ritin; McInnes, Susan; Batterham, Marijka; Zwar, Nick
Abstract: To evaluate the impact of general practice nurse‐led interventions for blood pressure control and cardiovascular disease risk factor reduction in patients with hypertension. Systematic review and meta‐analysis of randomized control trials. CINAHL, Medline and Scopus databases were searched to identify peer‐reviewed studies published between 2000 and 2021. A systematic review of randomized control trials was conducted using a structured search strategy. The Meta‐Analysis of Statistics Assessment and Review Instrument (JBI‐MAStARI) was used to appraise study quality. Meta‐analysis and narrative synthesis were performed to determine the effectiveness of the included interventions. Eleven trials comprising of 4454 participants were included in the review. Meta‐analysis showed significant reductions in both systolic and diastolic blood pressure in trials with 6 months or less follow‐up. Improvements were also demonstrated in reducing blood lipids, physical activity, general lifestyle measures and medication adherence. Evidence for dietary improvements and reduction in alcohol and smoking rates was inconclusive. Nurse‐led interventions for patients with hypertension are heterogeneous in terms of the nature of the intervention and outcomes measured. However, nurse‐led interventions in general practice demonstrate significant potential to improve blood pressure and support cardiovascular disease risk factor reduction. Future research should be directed towards elucidating the successful elements of these interventions, evaluating cost‐effectiveness and exploring translation into usual care. This review provides evidence that nurses in general practice could enhance current hypertension management through nurse‐led interventions.